Les exclamations cachées de la forme It’s astonishing the amount of anxiety in our society : l’enchâssement du syntagme nominal, entre rupture syntaxique et continuité sémantique - Olivia Reneaud-Jensen (Anglophonia)
This study questions the syntactic status of the NPs in exclamative constructions, such as It’s amazing the car he bought, that is to say in constructions in which the pronoun IT is followed by BE, by an emotive hyperbolic adjective such as amazing, and by a concealed exclamation (Elliott 1971) — a noun phrase with an exclamative interpretation (It’s amazing what a car he bought). In their surface structure, these constructions have the same complement selection as constructions such as You wouldn’t believe NP, I can’t believe NP or I’m amazed at NP. IT BE AMAZING is an embedding predicate selecting noun phrases. To be embedded, a noun phrase must meet semantic criteria (Grimshaw 1979). This paper reflects on the mechanisms at work in the embedding of the noun phrase after BE, by addressing the common semantic features and the differences within the category of concealed exclamations. It aims at identifying the syntactic, semantic, and pragmatic links between the noun phrase and the entire construction. To do so, it puts in regard the different underlying steps leading to the construction and the meaning and productivity of its surface structure. It shows that the construction is a form-meaning pairing, in which the embedding predicate IT BE ADJ is non-compositional, and functions in the same way as embedding predicates with the verbal structures believe, get over et be amazed at. This can be accounted for both by a rightward movement in its underlying structure and shared semantic features with all predicates that are compatible with concealed exclamations. The aim of this study is to link the semantic and pragmatic parameters which predict whether a noun phrase can be embedded, the constraints which motivate the underlying rightward movement, and tendencies in terms of lexical affinities and productivity drawn from observations taken from the COCA.